An actigraphy study of sleep and pain in midlife women: the Study of Women's Health Across the Nation Sleep Study. Issue 7 (July 2015) - Kravitz, Howard M.; Zheng, Huiyong; Bromberger, Joyce T.; Buysse, Daniel J.; Owens, Jane; Hall, Martica H.
Abstract: Objective: We examined whether women reporting nighttime pain would have more actigraphy-measured evidence for disturbed sleep and would report feeling less rested compared with women without nighttime pain. Methods: Up to 27 consecutive nights of actigraphy and sleep diary data from each participant were analyzed in this community-based study of 314 African-American (n = 118), white (n = 141), and Chinese (n = 55) women, aged 48 to 58 years, who were premenopausal, perimenopausal, or postmenopausal and were participating in the Study of Women's Health Across the Nation Sleep Study. Dependent variables were actigraphy-measured movement and fragmentation index, total sleep time, sleep efficiency, and diary self-report of "feeling rested" after waking up. All outcomes were fitted using linear mixed-effects models to examine covariate-adjusted associations between the independent variable (nighttime pain severity) and sleep outcomes. Results: Higher pain severity scores were associated with longer sleep duration but reduced sleep efficiency and less restful sleep. Women reporting nocturnal vasomotor symptoms had more sleep-related movement and sleep fragmentation, had reduced sleep efficiency, and were less likely to feel rested after wakening whether or not they reported pain. Conclusions: Midlife women who report higher nighttime pain levels have more objective evidence for less efficient sleep, consistent with self-reported less restful sleep. Nocturnal vasomotor symptoms also can contribute to restlessness and wakefulness in midlife women.